As diferentes facetas do trabalho do professor: dos órgãos governamentais à palavra do trabalho - Leite, Márcia Donizete (2009)
Based on the principle that a broader conceptualization of work may allow us to reach a more comprehensive awareness of what teachers work is (MACHADO, 2008), we analyzed an official educational document of the Government of State São Paulo (Curricular Proposal/2008) and texts written by some teachers of the Public Education Network of this State aiming at contributing to a better understanding of the teaching work. In this context, the general objective of the research is to investigate which constituent elements of the teaching work are constituted as a focus and evaluated in the texts of this official document and in the texts of the participant teachers, for this research may disclose factors that interfere in a significant way in teachers work actions. The analysis of these texts was carried through on the basis of the theoretical principles of ISD (Socio-discursive Interactionism), from a dialogic perspective, where work is seen as a way of acting whose configurations are constructed in language. Results allow us to detect that in the official text teaching work depends only on one of the elements focused by the Proposal, which are offered by its prescribers, while in the texts of the participant teachers we may see that teachers act in function of several constituent elements of their work. Thus, the research shows to be necessary a review of certain conceptions and a multidimensional perspective which give voice to these professionals, so that we may arrive at the improvement of prescriptions and thus contribute for the improvement of education, but also for rescuing the social values implied in the teaching work